UPAYA MENINGKATKAN MOTIVASI BELAJAR MELALUI BIMBINGAN KLASIKAL DENGAN MEDIA AUDIO VISUAL: LITERATUR REVIEW - Galuh Dhitya; Arbin Janu Setiyowati; Galuh Dhitya (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: Learning motivation is an important factor that influences students' academic success. Efforts to increase learning motivation can be done through classical guidance using audio-visual media. This literature review examines various studies, articles and journals related to the effectiveness of using audio-visual media in classical guidance to increase student learning motivation. The use of this media provides an opportunity to present information in a more interesting and meaningful way for students. The combination of visual media such as video, animation, pictures, and auditory media such as sound, music, or narration can stimulate students' senses of sight and hearing simultaneously. This facilitates a more effective learning process because information can be processed through multiple channels. Apart from that, audio visual media is also able to create a more interactive learning experience, so that it can increase student involvement and participation in guidance activities. With attractive visualizations and lively sound, this media can help capture students' attention and maintain their focus for longer periods of time. However, the effectiveness of using audio-visual media in classical guidance is also influenced by other factors such as the quality of the content presented, the facilitator's skills in integrating the media appropriately, and the suitability of the media to learning objectives and student characteristics. Therefore, careful planning and preparation is needed to ensure that the use of audio-visual media can really make a positive contribution to increasing student learning motivation